ANALYSIS OF THE INFLUENCE OF RATE, TYPE OF INSURANCE PRODUCT AND IMPLEMENTATION OF INSURANCE POLICY PREMIUM PAYMENT POLICY ON INSURANCE PRODUCT PURCHASE DECISION AT PT. BSAM MEDAN INSURANCE - Annisa Amelia; Paham Ginting; Endang Sulistya Rini (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
Talk about consumer purchasing behavior associated with the purchase of an insurance product, it will relate to answer the question of what type of insurance product that will be purchased, how much tariff should be issued by the holder of the policy premiums, and how the company's payments insurance policy. The problem in this study is the Tariff, Product Insurance Types and Insurance Premium Payment policies significantly influence the purchase decision of Insurance Products in PT BSAM Insurance Medan. The method used in this study is descriptive quantitative, and the nature of this study is explanotary research. The population in this study is 7590 totaled of insurance policyholders with a total sample of 400 respondents. The data analysis technique used in this study is multiple regression analysis. To test the hypothesis, F test was used to test simultaneously, and the t test for partial testing. The test results show that the hypothesis simultaneously (Test F) variable tariff, Products, and Insurance Premium Payment Policy has a positive and significant impact on Purchasing Decisions Insurance Products, while partial (t test) variable tariff and products has a positive and significant the decision to purchase insurance products in BSAM Insurance Medan, and variable insurance policy premium payment policy is not a positive and significant impact on the buying decision Insurance Products Insurance BSAM Medan.